Supplementary education in real estate management: new MBA programs - E. I. Ivankina (Moscow Polytechnic University, 2022)
The article looks at new MBA programs realized at the department of real estate management of the Russian Presidential Academy of National Economy and Public Administration. The supplementary education in the sphere of real estate gives wide opportunities both for studentsand lectures.